(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The Aim of this study is to compare the concentration of salivary leptin levels between underweight and normal weightindividuals and its significance in orthodontic tooth movement.Materials and Method: This observational study included forty-five underweight and normal weight female subjects and they aredivided into two groups, group I (underweight) and group II (normal weight) depending on their mean body mass index given by WHOclassification. All subjects underwent upper first premolar extraction, and distal force is applied with lacebacks to maxillary canine.Salivary leptin samples were collected before force application (To), one hour after appliance placement (T1), and one month afterappliance placement (T2).Result: Underweight individuals show decreased salivary leptin concentration than normal weight individuals. Orthodontic toothmovement is increased in underweight individuals when compared with normal weight individuals.Conclusion: Orthodontic tooth movement is increased in underweight patients when compared with normal weight patients. Salivaryleptin is two times greater in normal weight patients when compared with underweight patients.